Monoclonal Antibodies against Calcitonin Gene-Related Peptide: Only for Migraine Treatment? - Varžaitytė, Greta; Staškutė, Ugnė; Masiulienė, Ieva; Žemgulytė, Gintarė (Neurologijos seminarai, 2024)
This review aims to discuss the current literature on the effectiveness of monoclonal antibodies against calcitonin gene-related peptide (CGRP) in the treatment of non-migraine headaches. Based on recent articles, the pathophysiology of headaches and the role of CGRP in the pathogenesis of headaches are reviewed. In selected clinical trials and case studies, the efficacy of galcanezumab, fremanezumab and erenumab in the treatment of cluster headache, trigeminal neuralgia and post-traumatic headache was examined. The review reveals that CGRP is involved in the pathogenesis of various primary and secondary headache diseases. The efficacy of monoclonal antibodies against CGRP in the treatment of cluster headache and trigeminal neuralgia is currently based on clinical case studies, but further randomised placebo-controlled trials are still needed.
Keywords: monoclonal antibodies against calcitonin gene-related peptide; cluster headache; trigeminal neuralgia; post-traumatic headache; migraine